Edukasi Penyembuhan/Pemulihan Pasca Operasi pada Komunitas Lansia Surakarta - Suyanti Suyanti; Andang Sudarmono (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
The post-operative recovery process is an important aspect in improving the quality of life for the elderly. A proper understanding of wound care, pain management, and activities that can accelerate recovery is essential to support their healing. Therefore, appropriate education and counseling are needed to help the elderly manage their recovery process effectively. The aim of this community service activity is to improve the knowledge and skills of the elderly community in Surakarta regarding post-operative healing. The method used in this activity is a quantitative approach with a pre-experimental design consisting of a pre-test and post-test with one group. The respondents were 20 elderly individuals who had undergone surgery. A pre-test was conducted before the education to measure the initial knowledge level of the elderly regarding post-operative care. After providing education on wound care, pain management, and the importance of recovery activities, a post-test was conducted to measure changes in the elderly’s knowledge after receiving the education. The results of this activity showed a significant increase in the elderly’s knowledge, as indicated by the difference between pre-test and post-test scores. This demonstrates that the education provided was effective in enhancing the elderly’s understanding of post-operative care and recovery processes. This activity is expected to help the elderly recover more quickly and effectively, thereby improving their quality of life after surgery.